Modular total synthesis of rhizopodin: a highly potent G-actin dimerizing macrolide - Kretschmer, Manuel; Dieckmann, Michael; Li, Pengfei; Rudolph, Sven; Herkommer, Daniel; Troendlin, Johannes; Menche, Dirk (Chemistry - a European journal, 2013)
A highly convergent total synthesis of the potent polyketide macrolide rhizopodin has been achieved in 29 steps by employing a concise strategy that exploits the molecule′s C2 symmetry. Notable features of this convergent approach include a rapid assembly of the macrocycle through a site-directed sequential cross-coupling strategy and the bidirectional attachment of the side chains by means of Horner-Wadsworth-Emmons (HWE) coupling reactions. During the course of this endeavor, scalable routes for synthesis of three main building blocks of similar complexity were developed that allowed for their stereocontrolled construction. This modular route will be amenable to the development of syntheses of other analogues of rhizopodin.
Gesehen am 07.04.2021